Developmental approach to on-farm research: Pilot project for improving small ruminant production in humid West Africa - Atta-Krah, A.N. (International Center for Agricultural Research in the Dry Areas, 1985)
Describes the approach and methodologies adopted for on-farm research, including agronomy trial (alley farming) and veterinary trial, aimed at improving small ruminant production in Humid West Africa. Outlines the significant problems & opportunities created. Summarises the initial evaluation of alley farms in the LPU pilot project and vaccination records at two pilot villages, Own-Ile and Iwo-Ate. Shows the distribution of planting dates. Presents an integrated alley farming model activity schedule.